2003
DOI: 10.1021/ja0354418
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step in Situ Synthesis of Polymer-Grafted Single-Wall Nanotube Composites

Abstract: Single-wall carbon nanotubes (SWNTs) have been widely touted as attractive candidates for use as fillers in composite materials due to their extremely high Young's modulus, stiffness, and flexibility. 1 Successful applications of such composite systems require well-dispersed nanotubes with good adhesion with the host matrix, which, unfortunately, is not easily realized. Processing is rendered difficult by poor solubility of SWNTs, and the exfoliation of nanotube bundles is a major challenge. Moreover, inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
248
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(264 citation statements)
references
References 18 publications
7
248
0
4
Order By: Relevance
“…Sulfenylation and phosphonylation of carboanionic derivatives of carbon structures generated by the additions of alkyllithiums to native carbon nanotubes 21 . The fi rst system of the modifi ed MWCNT was obtained according to the process 23 .…”
Section: Functionalization Of Halogenated Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfenylation and phosphonylation of carboanionic derivatives of carbon structures generated by the additions of alkyllithiums to native carbon nanotubes 21 . The fi rst system of the modifi ed MWCNT was obtained according to the process 23 .…”
Section: Functionalization Of Halogenated Carbon Nanotubesmentioning
confidence: 99%
“…These reactions should lead to modifi ed CNT carbon nanotubes with the general structure (R*)4. The joining of heteroatoms containing salt to native carbon tubes is based on the reaction of carbanions generated by the addition to them of the salts with oxidizing solvents 21 . This will lead to the creation of derivatives of the native nanotubes with a direct carbon-heteroatom bond [structured CNT = (R) (Z), where R = alkyl and Z = R 1 S (O) or R1 R2 P (O)]…”
mentioning
confidence: 99%
“…It was also demonstrated that metallic SWNTs showed higher reactivity in these types of reactions than semiconductive SWNTs, which would allow CNT separation [134]. [135], CNTs were reacted with strong nucleophilic reagents such as nucleophilic carbene [128], sec-butyllithium [136], polymeric carbanions [137] and Birch reduction reagents (lithium/1,2-diaminoethane [108] or lithium/ammonia [138]) to form various f -CNTs (Scheme 3.4).…”
Section: Radical Additionmentioning
confidence: 99%
“…Various methods have been examined in efforts to overcome this problem, such as mechanical mixing [3], chemical functionalization of the tubes [4][5][6], and the utilization of organic [7,8] and polymeric surfactants [9] via non-covalent interactions. An in-situ polymerization [10], where nanotubes are incorporated into the prepolymer during the polymerization process, has been utilized to provide carbon nanotubes-reinforced composites with enhanced mechanical properties. On the other hand, the functionalization of carbon nanotubes is also very effective in preparing soluble carbon nanotubes by generating structural defects in strong acid [11,12], and inducing a chemical reaction between alkyl groups and azide moieties [13], and π-π interaction with electron-rich molecules [6,14].…”
Section: Introductionmentioning
confidence: 99%